Co-creation value: From time to time - Alexander Barus; Dwi Martiyanti; Hendri Sembiring; Piji Pakarti; Fajrillah Fajrillah (Faculty of Economics and Business, Universitas Mulawarman, 2023)
This literature review uses a systematic review approach and bibliographic analysis. The data source is google scholar, and the search for article data uses PoP by using the terms: